Mesenchymal Stem Cell Therapy for Diabetic Kidney Disease: A Review of the Studies Using Syngeneic, Autologous, Allogeneic, and Xenogeneic Cells - Christian Sávio-Silva; Stephany Beyerstedt; Poliana E. Soinski-Sousa; Expedito B. Casaro; Maria Theresa A. Balby-Rocha; Antônio Simplício-Filho; Jamille Alves-Silva; Érika B. Rangel (Hindawi Limited, 2020)
Diabetic kidney disease (DKD) is a microvascular complication of diabetes mellitus (DM) and comprises multifactorial pathophysiologic mechanisms. Despite current treatment, around 30-40% of individuals with type 1 and type 2 DM (DM1 and DM2) have progressive DKD, which is the most common cause of end-stage chronic kidney disease worldwide. Mesenchymal stem cell- (MSC-) based therapy has important biological and therapeutic implications for curtailing DKD progression. As a chronic disease, DM may impair MSC microenvironment, but there is compelling evidence that MSC derived from DM1 individuals maintain their cardinal properties, such as potency, secretion of trophic factors, and modulation of immune cells, so that both autologous and allogeneic MSCs are safe and effective. Conversely, MSCs derived from DM2 individuals are usually dysfunctional, exhibiting higher rates of senescence and apoptosis and a decrease in clonogenicity, proliferation, and angiogenesis potential. Therefore, more studies in humans are needed to reach a conclusion if autologous MSCs from DM2 individuals are effective for treatment of DM-related complications. Importantly, the bench to bedside pathway has been constructed in the last decade for assessing the therapeutic potential of MSCs in the DM setting. Laboratory research set the basis for establishing further translation research including preclinical development and proof of concept in model systems. Phase I clinical trials have evaluated the safety profile of MSC-based therapy in humans, and phase II clinical trials (proof of concept in trial participants) still need to answer important questions for treating DKD, yet metabolic control has already been documented. Therefore, randomized and controlled trials considering the source, optimal cell number, and route of delivery in DM patients are further required to advance MSC-based therapy. Future directions include strategies to reduce MSC heterogeneity, standardized protocols for isolation and expansion of those cells, and the development of well-designed large-scale trials to show significant efficacy during a long follow-up, mainly in individuals with DKD.